Epilepsy in four genetically determined syndromes of intellectual disability. (6th December 2011) - Leung, H. T. T.; Ring, H.
Abstract Background Epilepsy occurs with increased frequency in people with an intellectual disability (ID) compared to the rest of the population. A variety of research has in recent years shed light on genetic and biochemical aetiologies of epilepsy and, often in a different literature, on syndromes of ID. The aims of this annotation are to review developments in understanding of the pathophysiology of several ID syndromes in which epilepsy is a frequent co‐occurrence and to relate these observations to recent advances in understanding of how these pathophysiological disturbances may lead to epilepsy. Method The ID syndromes selected for review were fragile X (FXS), Rett (RTT) and Angelman syndromes (AS) and tuberous sclerosis complex (TSC). Epilepsy is a significant aspect of these syndromes and relevant research into the genetic and biochemical pathophysiology of these four ID syndromes may be informative in establishing the association between epilepsy and ID. Employing a structured approach the authors initially searched the PubMed database for large case series describing the characteristics of epilepsy as manifested in these ID syndromes. The criteria for inclusion of the case series in the review were a sample size of greater than 50 and the description of several of the characteristic features of epilepsy, namely prevalence of seizures, age of seizure onset, seizure frequency, seizure semiology, severity and treatment. Following this, studies of the genetic and biochemical pathophysiology of these four ID syndromes were reviewed and the potential relevance of this research in understanding the association with epilepsy highlighted. Findings were considered in a focused manner in terms of effects on excitatory and inhibitory neurotransmitter systems and on glial function. Results Diverse genetic pathologies underlying several ID syndromes can lead to alterations in the functioning of the glutamatergic and GABAergic neurotransmitter systems. The mechanisms involved include transcriptional regulation in RTT, translational regulation in FXS and TSC, and UBE3A‐mediated proteolysis in AS. Expression or functioning of receptor subunits, uptake sites and enzymes involved in neurotransmitter metabolism are often affected by these changes, and may lead to modifications in network excitability and neuronal plasticity that may contribute to epileptogenesis and ID. Dysfunction in astrocytes may also contribute to epileptogenesis and ID in FXS, RTT and TSC with potential mechanisms including failure of astrocytic support functions, glial inflammation and homeostatic disturbances that affect the excitability and architecture of neuronal networks. Conclusions The annotation highlights research describing disturbances in excitatory and inhibitory neurotransmitter systems, neuronal ion channel and glial functions that provide possible explanations for the co‐occurrence of seizures within several ID syndromes, in some cases suggesting possible avenues for research into novel therapeutic targets. Phenotypic overlaps between syndromes may also relate to roles for the implicated genes in different disturbances in linked biochemical pathways.